2018
DOI: 10.1186/s11671-018-2477-6
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared-Emitting Cr3+/Eu3+ Co-doped Zinc Gallogermanate Persistence Luminescent Nanoparticles for Cell Imaging

Abstract: Near infrared (NIR)-emitting persistent luminescent nanoparticles have been developed as potential agents for bioimaging. However, synthesizing uniform nanoparticles with long afterglow for long-term imaging is lacking. Here, we demonstrated the synthesis of spinel structured Zn3Ga2Ge2O10:Cr3+ (ZGGO:Cr3+) and Zn3Ga2Ge2O10:Cr3+,Eu3+ (ZGGO:Cr3+,Eu3+) nanoparticles by a sol-gel method in combination with a subsequent reducing atmosphere-free calcination. The samples were investigated via detailed characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…6, we present the visible emission spectra under excitation 343 nm of all these glass samples with two peaks at about 488 and 653 nm, which are assigned to the 2 T 2 / 4 A 2g and 4 T 2g ( 4 F) / 4 A 2g transitions of Cr 3+ . 17,43,45 As shown, the visible emission intensities of Cr 3+ /Yb 3+ co-doped bands centered at 488 and 653 nm signicantly increased with the increase in salt concentration ratio p from 0.18 to 0.54. 47 Interestingly, the peak at 488 nm of Cr 3+ under 343 nm excitation has a slight blue-shi of about 8 nm.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…6, we present the visible emission spectra under excitation 343 nm of all these glass samples with two peaks at about 488 and 653 nm, which are assigned to the 2 T 2 / 4 A 2g and 4 T 2g ( 4 F) / 4 A 2g transitions of Cr 3+ . 17,43,45 As shown, the visible emission intensities of Cr 3+ /Yb 3+ co-doped bands centered at 488 and 653 nm signicantly increased with the increase in salt concentration ratio p from 0.18 to 0.54. 47 Interestingly, the peak at 488 nm of Cr 3+ under 343 nm excitation has a slight blue-shi of about 8 nm.…”
Section: Resultsmentioning
confidence: 78%
“…These increments may be ascribed to the local surface plasmon resonance (LSPR) of copper ions 44 and the crystal eld variation caused by copper ions. 17,43,45 Moreover, the intensities of two absorption spectra bands centered at 306 nm and 878 nm also increased signicantly, which conrms the existence and the role of Cu + and Cu 2+ , respectively, 46 in the absorption spectra of Cr 3+ /Yb 3+ co-doped. The Cu + formed and exists in silicate glass due to reducing of Cu 2+ .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…PLNPs exhibit unprecedented advantages in stem cells tracking due to the following unique features 104. The most important is that PLNPs can remain glowing for hours or even days after excitation is stopped,105107 which makes long-term imaging possible without in situ excitation. The other is that PLNPs have excellent signal-to-noise ratios, and can be distinguished from normal tissue autofluorescence.…”
Section: Nps and Their Toxic Effectsmentioning
confidence: 99%
“…Most of the research is focused on the exploration of Zn 3 Ga 2 Ge 2 O 10 (ZGG) doped with Mn 2+ , Bi 3+ , and Cr 3+ for their PL and/or PerL properties owing to its low synthesis temperature, high stability, excellent bio-compatibility, non-toxicity, and moderate conductivity. 1,4,18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, there are very few reports on intrinsic self-activated bluish white emission in bulk/microcrystalline ZGG. 29 Although Li et al 18 have demonstrated the visible PL in ZGG nanoparticles, their emission zone lies more in the green region which lacks commercial usage for day to day activity compared to white light emitting materials.…”
Section: Introductionmentioning
confidence: 99%